2006
DOI: 10.1097/01.ta.0000196700.74272.10
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Malleolar Fracture is Often Associated with Spiral Tibial Diaphyseal Fracture: A Retrospective Study

Abstract: A fracture of the posterior malleolus was involved in every fourth tibial diaphyseal fracture. The fractures of the posterior malleolus were always detected in preoperative plain films and should be suspected, especially in cases of low-energy spiral distal tibial diaphyseal fractures. We recommend additional plain films to be taken at the ankle region to better visualize these fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 5 publications
4
35
0
Order By: Relevance
“…However, none of their nondisplaced posterior malleolar fractures became displaced after nailing. In another study, 66% of nondisplaced fragments were not internally fixed, and they reported no subsequent problems in these patients Delayed/missed diagnosis of associated posterior malleolus fracture 2 (5%) 0 [11]. Georgiadis et al conversely reported four patients in their series had intraoperative displacement of the posterior malleolus, all of which were unrecognized preoperatively [6] (Table 2).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, none of their nondisplaced posterior malleolar fractures became displaced after nailing. In another study, 66% of nondisplaced fragments were not internally fixed, and they reported no subsequent problems in these patients Delayed/missed diagnosis of associated posterior malleolus fracture 2 (5%) 0 [11]. Georgiadis et al conversely reported four patients in their series had intraoperative displacement of the posterior malleolus, all of which were unrecognized preoperatively [6] (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…Van der Werken and Zeegers, however, reported a rate of 11.5% [18]. A more recent study reported a higher incidence of 25% [11]. Most likely, the variably reported rates are secondary to increased detection with improved imaging quality and increased awareness of the association.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, all the PMFs were due to the original trauma, and not iatrogenic due to nailing procedure. 7 However, the nailing procedure may displace the fragment. 1,2 This occurs as a result of overaggressive reaming, or the use of too large and long nail, which was iatrogenic displacement not iatrogenic fracture (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 These injuries may occur isolated or in combination with other injuries, such as, trimalleolar fractures, proximal fibular fractures, syndesmotic injuries or low-energy tibial shaft spiral-type fractures. 3,4,8 In this line, Kukkonen and colleagues reported that a fourth of the tibial shaft spiral-type fractures were associated with posterior malleolus fractures. 8 Usually, these fractures are related to a specific injury mechanism comprising, plantar flexion in axial load at the moment of ground impact, supination or external rotation of the talus in axial load, or progressive external rotation of the talus.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,8 In this line, Kukkonen and colleagues reported that a fourth of the tibial shaft spiral-type fractures were associated with posterior malleolus fractures. 8 Usually, these fractures are related to a specific injury mechanism comprising, plantar flexion in axial load at the moment of ground impact, supination or external rotation of the talus in axial load, or progressive external rotation of the talus. 9 Given the need to standardize the diagnosis and complementary imaging procedures on ankle injuries, Stiell and collaborators created the "Ottawa Ankle Rules", a clinical and radiological decision algorithm aiming to reduce the high number of radiographs made at the ankle joint, often considered unnecessary.…”
Section: Introductionmentioning
confidence: 99%